2008
DOI: 10.2528/pier08072901
|View full text |Cite
|
Sign up to set email alerts
|

Image Reconstruction of the Buried Metallic Cylinder Using FDTD Method and Ssga

Abstract: Abstract-This paper presents an image reconstruction approach based on the time-domain and steady state genetic algorithm (SSGA) for a 2-D perfectly conducting cylinder buried in a half-space. The computational method combines the finite difference time domain (FDTD) method and the steady state genetic algorithms (SSGA) to determine the shape and location of the subsurface scatterer with arbitrary cross section. The subgirdding technique is implemented in the FDTD code for modeling the shape of the cylinder mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
(31 reference statements)
0
10
0
Order By: Relevance
“…For time-domain algorithms, where the shape reconstruction of conducting scatterers is a concern, PSO has been investigated, whereas the steady-state GA (SSGA) has been utilized in the reconstruction of metallic scatterers (Huang et al, 2008). In this case, the reported results indicate that PSO is a reliable tool for inverse scattering applications.…”
Section: Introductionmentioning
confidence: 93%
“…For time-domain algorithms, where the shape reconstruction of conducting scatterers is a concern, PSO has been investigated, whereas the steady-state GA (SSGA) has been utilized in the reconstruction of metallic scatterers (Huang et al, 2008). In this case, the reported results indicate that PSO is a reliable tool for inverse scattering applications.…”
Section: Introductionmentioning
confidence: 93%
“…Evaluate the population using objective function: the PSO algorithm evaluates the objective function (9) for each individual in the population.…”
Section: Psomentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][17][18][19] Among these techniques, the PSO is the most recent one and is never used to deal with the imaging problem of buried conducting cylinders to the best of our knowledge; an anti-noise study about the performances of PSO has not yet been reported with application to the electromagnetic inverse scattering problems.…”
Section: Introductionmentioning
confidence: 99%
“…In general, they tend to get trapped in local minima when the initial trial solution is far from exact. Thus, some population-based stochastic methods, such as the genetic algorithm (GA) (Huang et al, 2007(Huang et al, , 2008bCaorsi et al, 2000;Zhong et al, 2007), particle swarm optimization (PSO) (Rekanos & Trochidis, 2007;Donelli & Massa, 2005;Huang et al, 2008a;Travassos et al, 2008), and differential evolution (DE) (Michalski, 2000;Qing, 2003), have been proposed to search the global extreme of the inverse problem to overcome the drawback of the deterministic methods. In the 2006, the dynamic DE (DDE) was first proposed to deal with the shape reconstruction of the conducting cylinder (Qing, 2006).…”
Section: Introductionmentioning
confidence: 99%